Reactive Intravascular Plasmablastic/Immunoblastic Proliferation in a Patient with Concurrent Gastric Mucosa-Associated Lymphoid Tissue Lymphoma and Tuberculosis Potentially Mimicking Aggressive Intravascular Lymphoma: A Rare Case Report - Ling Ling Zhong; Zhi Ping Tang; Hai Peng Zhang; Shuang Zhong; Ying Wen Huang; Gao Xiang Huang (Case Reports in Gastroenterology)
Introduction: Reactive intravascular plasmablastic/immunoblastic proliferation (RIVPIP) is rarely reported. RIVPIP may histologically mimic aggressive intravascular lymphoma, especially in the context of an old patient presenting with concurrent indolent lymphoma and tuberculosis, and easily lead to erroneous diagnosis. Case Presentation: A 79-year-old female presenting with upper abdominal discomfort, weight loss, hypoproteinemia, and polyserosal effusions underwent a gastric endoscopy examination. Biopsy revealed that the lamina propria was infiltrated by a large number of uniformly small-sized lymphocytes (CD20+/PAX5+) with lymphoepithelial lesions and epithelioid granuloma. Notably, vascular lumens were filled and distended by abundant large-sized plasmablasts or immunoblasts (CD79α+/MUM1+/CD20-/CD138-/PAX5-/CD30-/Bcl-2-/Bcl-6-/C-myc-). These intravascular large lymphoid cells demonstrated high proliferative activity (Ki67 >80%) without immunoglobulin light chain restriction or EBV association (EBER-ISH negative). Furthermore, PCR revealed monoclonal rearrangements in IgH, IgK, and IgL genes. The patient had a history of endoscopic gastric biopsy 2 months ago. Retrospective analysis of a prior biopsy identified conspicuous caseating necrosis, epithelioid granuloma, multinucleated giant cells with suspicious positivity for acid-fast staining, highly suggestive of tuberculosis. Based on two biopsy specimens and systemic symptoms, the case was finally diagnosed as gastric MALT lymphoma and tuberculosis with extensive RIVPIP. Conclusion: We present an unusual case of RIVPIP with severe systemic symptoms due to concurrent gastric MALT lymphoma and tuberculosis, emphasizing a potential diagnostic pitfall for clinical pathologists in distinguishing RIVPIP from the aggressive intravascular lymphoma. A comprehensive evaluation of clinical manifestations, pathological morphology, immunophenotype and gene analysis is required to make the precise diagnosis.